Repurposing Metformin and Antifolates for the Treatment of Hepatocellular Carcinoma - Mohamed Tawfik, Sherouk (AUC Knowledge Fountain, 2022)
Hepatocellular carcinoma (HCC), one of the most prevalent types of cancers worldwide, continues to maintain high levels of resistance to standard therapy. As clinical data revealed poor response rates, the need for developing new methods has increased to improve the overall wellbeing of patients with HCC. Due to its safety, wide availability and previously reported anti-cancer effects, metformin (MET) serves to be a possible therapeutic agent when combined with other well-known anti-cancer agents. The aim of this study was to investigate the potential anti-cancer effects of MET, an anti-diabetic agent, when combined with two antifolate drugs: trimethoprim (TMP) or methotrexate (MTX), and the underlying mechanisms involved. In this study, single drugs and combinations were investigated using in vitro assays, cytotoxicity assay (MTT), RT-PCR, flow cytometry, scratch wound assay and Seahorse XF analysis, to reveal their potential anti-cancer effects on a human HCC cell line, HepG2. The cytotoxicity assay was performed to determine the IC50 concentration of MET alone and in combination with antifolates. The co-treatment of both drugs increased Bax and p53 apoptotic markers, while decreased the anti-apoptotic marker; Bcl-2. Both combinations increased the percentage of apoptotic cells and halted cancer cell migration, when compared to MET alone. Furthermore, both combinations decreased the MET-induced increase in glycolysis, while also induced mitochondrial damage, altering cancer cell bioenergetics. This study introduces two novel therapeutic combinations, which enhance the anti-proliferative and apoptotic effects of MET on HepG2 cells, and hence, potentially combat the aggressiveness of HCC.